2017
DOI: 10.1128/mbio.01586-16
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Combination Therapy for Tuberculosis: Lessons for Future Antimicrobial Development and Application

Abstract: Tuberculosis is a global health problem that causes the death of approximately 1.5 million people worldwide each year (WHO, p. 1–126, Global Tuberculosis Report, 2015). Treatment of drug-susceptible tuberculosis requires combination antimicrobial therapy with a minimum of four antimicrobial agents applied over the course of 6 months. The first instance of combination antimicrobial therapy applied to tuberculosis was the joint use of streptomycin and para-aminosalicylic acid as documented by the Medical Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 80 publications
3
112
0
Order By: Relevance
“…Goldie and Coldman's seminal results in the 1980s demonstrated that this strategy reduces the emergence of resistance in cancer cells, maximising the probability of remission [149][150][151][152]. A similar approach has been successfully applied to the management of several diseases, ranging from HIV [153] and TB [154] to rheumatoid arthritis [155]. It is curious that HD, a disease genotypically present at birth, takes decades to manifest clinically.…”
Section: Resultsmentioning
confidence: 99%
“…Goldie and Coldman's seminal results in the 1980s demonstrated that this strategy reduces the emergence of resistance in cancer cells, maximising the probability of remission [149][150][151][152]. A similar approach has been successfully applied to the management of several diseases, ranging from HIV [153] and TB [154] to rheumatoid arthritis [155]. It is curious that HD, a disease genotypically present at birth, takes decades to manifest clinically.…”
Section: Resultsmentioning
confidence: 99%
“…Drug repurposing is a useful strategy to accelerate the drug development process due to lower costs, reduced risk and decreased time to availability of preclinical data [89]. In studies pioneering the concept, rational combination chemotherapy was developed for tuberculosis and other bacterial infections [90]. Nowadays, its use has been extended for chemotherapy of cancer, acquired immune deficiency syndrome (AIDS) [91] and for malaria [92,93].…”
Section: Chemotherapy Against Schistosomiasis and Opisthorchiasismentioning
confidence: 99%
“…Nowadays, its use has been extended for chemotherapy of cancer, acquired immune deficiency syndrome (AIDS) [91] and for malaria [92,93]. The major goals of combination chemotherapy are to minimize and/or to delay the appearance of drug resistance [90][91][92], and to achieve an additive/synergistic effect that could translate in reduced doses of drugs and/or minimized side effects [90]. Ideally for opisthorchiasis and schistosomiasis, the combined drugs would exhibit a divergent mechanism of action of PZQ and/or target the immature parasite to enhance cure and eggs reduction rates as well as pathologies associated with infection and thereby improve the chemotherapy [65].…”
Section: Chemotherapy Against Schistosomiasis and Opisthorchiasismentioning
confidence: 99%
“…Tuberculosis (TB), caused by an aerobic, acid-fast bacillus, that is, Mycobacterium tuberculosis (M. tuberculosis), to humans, and it is still a major public health problem worldwide (Kerantzas and Jacobs 2017). For many decades, it has continued to pose a significant threat to human health (WHO 2017).…”
Section: Introductionmentioning
confidence: 99%